Evaluasi Formulasi Sediaan Lipstik Dari Sari dan Ekstrak Buah Harimonting - Siska Futri Nasution; Susilawati Harahap; Lathipah Hannah Lubis (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
Harimonting fruit (Rhodomyrtus tomentosa) has the potential to be used as an alternative dye because it has an attractive color. The dark purple color of Harimonting fruit is due to the presence of flavonoids, tannins, and steroids. From several components including Nipagin, Cera alba, BHT, Oleum ricini, Vaseline alba, Lanolin, Cetyl alcohol, Profiln glycol, Carnauba wax, Harimonting Fruit Extract with a concentration of 14%, 22% and 30-% and Harimonting Fruit Extract (Rhodomyrtus tomentosa) with concentrations of 10%, 13%, and 16%. Harimonting fruit (Rhodomyrtus tomentosa) was carried out by Maceration method with 75% ethanol as solvent. Lipstick preparations from Sari and Harimonting Fruit Extract (Rhodomyrtus tomentosa) resulted in a pH test of 4.4-5.4 (close to lip pH 4.0-6.5), melting point of 55.3-55.6˚C met the point requirements the melting point of lipstick (50-70˚C), the preparation of lipstick from the Harimonting fruit juice (Rhodomyrtus tomentosa) does not cause irritation when applied, it shows the presence of uneven red granules so that the lipstick preparation from the Harimonting fruit juice (Rhodomyrtus tomentosa) cannot be used as a natural dye for making lipstick, while Lipstick Preparations from Harimonting Fruit Extract (Rhodomyrtus tomentosa) do not cause irritation and are evenly distributed and easily smeared so that they can be used as natural dyes for making lipstick.